(untitled) (Malaysian Management Journal, 1997)
The balance of economic power is beginning to shift. A lively debate is in progress in Europe about the social and political consequences of the growing competition from emerging southeast Asian countries. This article provides a broad outline of the background behind the dynamism and the driving farces of globalization. Leading corporations adapt themselves- to the changing environmental conditions by using the strategies of global localization. and decentralized organizational structures (lean production, total quality management, reengineering etc.). Their success, however; depends on the development of the relevant institutions, not the least for regulating conflicts.